(untitled) - Government of Viet Nam (Viet Nam, 1992)
Contents: Mekong Delta land elevation, Mekong Delta water levels, Mekong Delta salt intrusion, Mekong Delta tidal irrigation and drainage...
Keywords: Water resources development; Mekong River Watershed,Evaluation